factorise.. with steps
Attachments:
![](https://hi-static.z-dn.net/files/d6b/4e86b44ca16ebbb887f5bf85e42affd8.jpg)
Answers
Answered by
1
Solution :
x² + 7xy + 12y²
Splitting the middle term , we get
= x² + 3xy + 4xy + 12y²
= x( x + 3y ) + 4y ( x + 3y )
= ( x + 3y )( x + 4y )
•••••
x² + 7xy + 12y²
Splitting the middle term , we get
= x² + 3xy + 4xy + 12y²
= x( x + 3y ) + 4y ( x + 3y )
= ( x + 3y )( x + 4y )
•••••
Answered by
1
hey mate
here is ur answer is in given attachment
● I hope it helps you
plz mark as brainliest plz
here is ur answer is in given attachment
● I hope it helps you
plz mark as brainliest plz
Attachments:
![](https://hi-static.z-dn.net/files/d09/cf80c83d4d235966390ce882a42a4aca.jpg)
Similar questions